Diversidade de colletotrichum spp. Agente etiológico da seca dos frutos de açaizeiro no estado do pará, brasil - Alves, Kezia Ferreira (Universidade Federal Rural do Semi-Árido, 2017)
The açaizeiro (Euterpe oleracea) is a species of the family Arecaceae and occurs spontaneously in the Brazilian Amazon. This plant has great socioeconomic importance for the region. Droght Fruits is a disease of the açaí crop that affects the yield of pulp. This work aims to study the diversity of the fungus Colletotrichum spp. by means of morphological, cultural, physiological and genetic characterizations. After the laboratory procedures, 20 samples of the fungus were submitted to pathogenicity tests, morphological and cultural characterization; physiological assessments and genetic sequencing. All fungus samples fulfilled Postulates of Koch. With this, it was possible to show in the morpho-cultural characterization 3 types of conidia, changes in colony coloration and orange conidial mass in most fungus samples. Temperatures between 24.05°C and 27.89°C determined the highest rates of mycelial growth rate (IVCM) of the fungi tested. The results of the genetic sequencing of the ITS5.8S and β-tubulin regions agreed with the morphological characterization of the fungus and presented similar sequences for the C. gloeosporioides complex. The PCR-ITS product evidenced different patterns for the enzymes AluI, HhaI, MspI and RsaI demonstrating the specificity of these enzymes for açaí Colletotrichum. Thus, it was possible to prove that there is genetic variability among the samples cataloged for fungi of the complex Colletotrichum gloeosporioides, etiological agent of the drought of açaizeiro fruits in the State of Pará
Keywords: Etiologia; Seca dos Frutos; Filogenia; Enzimas de restrição; Etiology; Fruit Drought; Phylogeny; Restriction Enzymes; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA